2019
DOI: 10.3390/molecules24193489
|View full text |Cite
|
Sign up to set email alerts
|

Atroxlysin-III, A Metalloproteinase from the Venom of the Peruvian Pit Viper Snake Bothrops atrox (Jergón) Induces Glycoprotein VI Shedding and Impairs Platelet Function

Abstract: Atroxlysin-III (Atr-III) was purified from the venom of Bothrops atrox. This 56-kDa protein bears N-linked glycoconjugates and is a P-III hemorrhagic metalloproteinase. Its cDNA-deduced amino acid sequence reveals a multidomain structure including a proprotein, a metalloproteinase, a disintegrin-like and a cysteine-rich domain. Its identity with bothropasin and jararhagin from Bothrops jararaca is 97% and 95%, respectively. Its enzymatic activity is metal ion-dependent. The divalent cations, Mg2+ and Ca2+, enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…We regard this fact as an exclusive event of the in vitro condition and not representative of an enzymatic characteristic involved in the biological action of Pic-III. In the presence of Ca 2+ and Mg 2+ , Pic-III significantly increases its proteolytic activity in line with SVMPs [ 30 , 42 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We regard this fact as an exclusive event of the in vitro condition and not representative of an enzymatic characteristic involved in the biological action of Pic-III. In the presence of Ca 2+ and Mg 2+ , Pic-III significantly increases its proteolytic activity in line with SVMPs [ 30 , 42 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was obtained according to Vivas-Ruiz et al [ 29 ]. The gene of Pic-III was amplified with the kit Master Mix Platinum ® Taq DNA Polymerase (Invitrogen, Carlsbad, CA, USA) according to the manufacturer’s instructions using the external primers MpIIIF and MpIIIR and the internal primers MpIIIFi and MpIIIRi provided by Oliveira et al [ 30 ]. The Pic-III gene expression level was analyzed according to Vivas-Ruiz et al [ 28 ] using Verso 1-Step qPCR ROX Kit (ThermoFisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several reports of alteration in ligand-receptor interaction; such alteration corresponds to the ectodomain sheddase activities of this domain ( Ho et al, 2002 ; Moura-da-Silva et al, 1996 ; Moura-da-Silva and Baldo, 2012 ). For instance, Oliveira et al (2009) showed how atroxlysin-III from the Peruvian pit viper snake ( Bothrops oligolepis ) induced glycoprotein VI shedding, culminating into platelet dysfunction ( Oliveira et al, 2019 ). Previously, the sheddase activity of atrolysin a, a P-III SVMP from Crotalus atrox venom, was demonstrated against collagen IV and annexin in cultured human fibroblasts ( Pinto et al, 2007 ).…”
Section: Domains Functionsmentioning
confidence: 99%